2019
DOI: 10.1016/j.ophtha.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Eyes Lost to Follow-up with Proliferative Diabetic Retinopathy That Received Panretinal Photocoagulation versus Intravitreal Anti–Vascular Endothelial Growth Factor

Abstract: Eyes with PDR that received only intravitreal anti-VEGF demonstrated worse anatomic and functional outcomes after being LTFU compared with eyes that received PRP. Given the potential sequelae of being LTFU, the choice of treatment for PDR must be considered carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
129
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 17 publications
1
129
2
4
Order By: Relevance
“…Most patients with DR, who were lost to follow-up, had no subsequent follow-up after 6 (74.6%) or 12 months (83.5%). In the studies conducted by Obeid et al [4,14], the insurance status of patients was not documented, and the expense of treatment and follow-up examinations may have greatly influenced the adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with DR, who were lost to follow-up, had no subsequent follow-up after 6 (74.6%) or 12 months (83.5%). In the studies conducted by Obeid et al [4,14], the insurance status of patients was not documented, and the expense of treatment and follow-up examinations may have greatly influenced the adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients are prone to significant loss to follow up due to illness, financial hardship, and lack of compliance. The rate of complications and loss of vision after unintentional interruptions for more than 6 months in PDR patients treated only on anti-VEGF was considerably higher than the eyes that received PRP, with a significantly higher number of eyes with tractional retinal detachment and neovascularization of the iris [102]. In a retrospective review of 13 eyes treated exclusively with anti-VEGF for PDR with or without macular edema or severe NPDR with macular edema, with hiatus of 12 months, 9 presented with vitreous hemorrhage, 5 with neovascular glaucoma, and 4 with tractional retinal detachment.…”
Section: Management Of Proliferative Diseasementioning
confidence: 81%
“…Another retrospective cohort study (Obeid et al, 2018), with 2303 patients enrolled, reported a higher rate of loss to follow-up (LTFU) in PRP group, which may be explained by its more durable effect, higher pain level (Lucena CRF de et al, 2013) and some complications. Obeid et al, 2019(Obeid et al, 2019 further investigated 59 PDR patients who were LTFU for over 6 months, in which anti-VEGF monotherapy manifested worse anatomic and functional outcomes. Wei et al (2017) also reported that fibronectin and fibrinogen concentrations in vitreous humor of intravitreal anti-VEGF injection group, which might promote fibrosis in eyes with PDR.…”
Section: Discussionmentioning
confidence: 99%